Ligand-Binding Affinity at the Insulin Receptor Isoform-A and Subsequent IR-A Tyrosine Phosphorylation Kinetics are Important Determinants of Mitogenic Biological Outcomes - Rajapaksha, Harinda; Forbes, Briony E. (Frontiers in Endocrinology, 2015)
The insulin receptor (IR) is a tyrosine kinase receptor that can mediate both metabolic and mitogenic biological actions. The IR isoform-A (IR-A) arises from alternative splicing of exon 11 and has different ligand binding and signaling properties compared to the IR isoform-B. The IR-A not only binds insulin but also insulin-like growth factor-II (IGF-II) with high affinity. IGF-II acting through the IR-A promotes cancer cell proliferation, survival, and migration by activating some unique signaling molecules compared to those activated by insulin. This observation led us to investigate whether the different IR-A signaling outcomes in response to IGF-II and insulin could be attributed to phosphorylation of a different subset of IR-A tyrosine residues or to the phosphorylation kinetics. We correlated IR-A phosphorylation to activation of molecules involved in mitogenic and metabolic signaling (MAPK and Akt) and receptor internalization rates (related to mitogenic signaling). We also extended this study to incorporate two ligands that are known to promote predominantly mitogenic [(His4, Tyr15, Thr49, Ile51) IGF-I, qIGF-I] or metabolic (S597 peptide) biological actions, to see if common mechanisms can be used to define mitogenic or metabolic signaling through the IR-A. The threefold lower mitogenic action of IGF-II compared to insulin was associated with a decreased potency in activation of Y960, Y1146, Y1150, Y1151, Y1316, and Y1322, in MAPK phosphorylation and in IR-A internalization. With the poorly mitogenic S597 peptide, it was a decreased rate of tyrosine phosphorylation rather than potency that was associated with a low mitogenic potential. We conclude that both decreased affinity of IR-A binding and kinetics of IR-A phosphorylation can independently lead to a lower mitogenic activity. None of the studied parameters could account for the lower metabolic activity of qIGF-I.